Biological and substitute parents in Beaker period adult–child graves - Nicoletta Zedda; Katie Meheux; Jens Blöcher; Yoan Diekmann; Alexander V. Gorelik; Martin Kalle; Kevin Klein; Anna-Lena Titze; Laura Winkelbach; Elise Naish; Laurent Brou; François Valotteau; et al. (Scientific Reports, 2023)
Abstract Joint inhumations of adults and children are an intriguing aspect of the shift from collective to single burial rites in third millennium BC Western Eurasia. Here, we revisit two exceptional Beaker period adult–child graves using ancient DNA: Altwies in Luxembourg and Dunstable Downs in Britain. Ancestry modelling and patterns of shared IBD segments between the individuals examined, and contemporary genomes from Central and Northwest Europe, highlight the continental connections of British Beakers. Although simultaneous burials may involve individuals with no social or biological ties, we present evidence that close blood relations played a role in shaping third millennium BC social systems and burial practices, for example a biological mother and her son buried together at Altwies. Extended family, such as a paternal aunt at Dunstable Downs, could also act as ‘substitute parents’ in the grave. Hypotheses are explored to explain such simultaneous inhumations. Whilst intercommunity violence, infectious disease and epidemics may be considered as explanations, they fail to account for both the specific, codified nature of this particular form of inhumation, and its pervasiveness, as evidenced by a representative sample of 131 adult–child graves from 88 sites across Eurasia, all dating to the third and second millennia BC.